(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Terrorismo e fenomeno religioso - 2. Politiche della sicurezza e diritti fondamentali - 3. La legislazione italiana contro il terrorismo nell’interpretazione giurisprudenziale - 4. Misure di prevenzione. Ampliamento delle categorie di pericolosità qualificata e prescrizioni atipiche - 5. Misure di prevenzione e libertà religiosa - 6. Best practice. Il provvedimento del Tribunale di Bari, Misure di Prevenzione, n. 71 del 2017 - 7. Il percorso di de-radicalizzazione. Religious prevention and de-radicalization measures to the test of secularity (at the margin of some of the Court’s measures of Bari). The article examines how the terrorist emergence of Islamic matrix has reproached the issue of reconciliation between the need for security and the protection of the rights of liberty, in particular religious freedom. It highlights the need to accompany, to purely punitive nature rules, the spread of a novel paradigm, covering preventive interventions, educational and formative, in order to promote intercultural and inter-religious integration. The decree of the court, which, in accordance with the principle of secularism, has prescribed, in view of the social recovery of the subject proposed for the application of the prevention measure, a process of de-radicalization, through the involvement of an intercultural mediator, on the basis of Guide-lines developed by the University of Bari.